Bioinformatics deciphers the thebaine biosynthesis pathway in opium poppy: Hub genes, network analysis, and miRNA regulation - Zahra Shirazi; Mahsa Rostami; Abozar Ghorbani; Pietro Hiram Guzzi (Journal of Genetic Engineering and Biotechnology)
Thebaine, a vital precursor in the codeine and morphine pathway, shows promise in addiction treatment. We conducted a comprehensive study on the thebaine biosynthesis pathway in opium poppy, utilizing bioinformatics tools. The dataset comprising the thirteen genes associated with the thebaine biosynthesis pathway was compiled from an extensive review of published literature and validated using the NCBI BLAST tool. Utilizing STRING and Cytoscape, we analyzed gene interactions and visualized the molecular interaction network, respectively. To identify hub proteins, CytoHubba was administered. The Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) at STRING were used for the enrichment analysis of the hub genes. CytoCluster was used to analyze the network in clusters. Promoter regions of hub genes and potential miRNAs were explored using MEME and the psRNATarget database. Hub genes crucial to thebaine biosynthesis were identified, contributing to essential cellular functions like growth, development, stress response, and signal transduction. Metabolic processes emerged as pivotal for thebaine production, indicating a broader role for the thebaine pathway gene network beyond primary metabolite production. Cell component subnetwork genes demonstrated associations with anatomical units, indicating involvement in plant defense responses. Dominant molecular functions drove plant defense responses. KEGG pathway analysis highlighted the significance of metabolic pathways and biosynthesis of secondary metabolites. Cluster analysis emphasized the relevance of the biosynthesis of amino acids, confirming the link between primary and secondary metabolites. Promoter analysis suggested the potential involvement of signal transduction in thebaine production. Hub genes were targeted by 40 miRNAs, suggesting potential novel biomarkers or target genes within the thebaine biosynthesis pathway. Based on the role of miRNAs identified in connection with the hub genes of the thebaine production process, the secondary metabolite pathway of thebaine appears to be associated with several key plant pathways, e.g. growth, development and stress response. However, these findings, based on bioinformatics analysis, warrant further experimental validation and promise to advance our understanding of the biosynthesis of thebaine and its interactions with other genes and metabolic pathways that influence the production of metabolites.